2017
DOI: 10.1038/s41598-017-17881-2
|View full text |Cite
|
Sign up to set email alerts
|

No evolutionary change in the mating system of Solanum rostratum (Solanaceae) during its invasion in China

Abstract: The mating system of flowering plants plays a key role during the process of invasion. Evolution from outcrossing to selfing can allow rapid regeneration of a population after long-distance dispersal by providing reproductive assurance. Solanum rostratum is a self-compatible annual herb that exhibits a high level of outcrossing in its native populations. However, the mating system of invasive populations of S. rostratum has never been assessed. Here, we investigated the mating system based on 11 microsatellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Consistent with our hypothesis, S. rostratum with low‐nutrient requirements (Feng, 2020; Juan et al, 2013; Zhang et al, 2017; Zhao et al, 2013) showed lower growth plasticity than its related native species S. nigrum under both high and low soil nutrient environments. The lower growth plasticity of the invasive relative to the native species reduced its growth disadvantage when decreasing soil nutrients, contributing to its invasiveness under low (but not high) nutrient environment.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Consistent with our hypothesis, S. rostratum with low‐nutrient requirements (Feng, 2020; Juan et al, 2013; Zhang et al, 2017; Zhao et al, 2013) showed lower growth plasticity than its related native species S. nigrum under both high and low soil nutrient environments. The lower growth plasticity of the invasive relative to the native species reduced its growth disadvantage when decreasing soil nutrients, contributing to its invasiveness under low (but not high) nutrient environment.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with our hypothesis, S. rostratum with low-nutrient requirements (Feng, 2020;Juan et al, 2013;Zhang et al, 2017;Zhao et al, 2013) showed lower growth plasticity than its related native promoting its invasion. Similarly, the marginally (P = 0.058) lower growth plasticity of the invasive species E. canadensis may also contribute to its invasiveness under low soil nutrient environment.…”
Section: Effects Of Growth Plasticity On Invasivenesssupporting
confidence: 86%
See 2 more Smart Citations
“…Most obviously, pollinators often facilitate self‐pollination within (facilitated autogamy) or among (geitonogamy) a plant's flowers (Harder and Barrett, 1995; Eckert, 2000; Owen et al, 2007), the incidence of which can vary among populations (Christopher et al, 2021). In addition, population differences in outcross‐mate diversity (Sun and Ritland, 1998; Yates et al, 2007; Zhang et al, 2017) must arise from variation in processes specifically involved in cross‐pollination.…”
mentioning
confidence: 99%